Cotton and Textile Industries in Egypt: Constraint and Opportunity - MOHAMED NEGM; SUZAN SANAD (Cotton Research Journal, 2023)
This paper takes a close look at the agricultural policies, addressing the Egyptian cotton production sector, and policies that can potentially increase the competitiveness of Egypt’s textile supply chain. It also suggests strategies to develop the textile and apparel sector of Egypt. This is an important pillar of the country’s Vision 2030 strategy, which is why the sector is promoted by a comprehensive set of policies and institutions. These initiatives are aimed to improve the vertical integration of the sector, modernize the industry, increase exports, and create employment. Further, this paper specially focuses on the economic importance of Cotton in Egypt, the previous achievements in the cotton sector by different relevant national and international entities, the recommendations on potential future actions to enhance productivity, value, and export of this commodity. The outcome of this paper is to provide a strategic Blueprint to enhance the competitiveness of the total cotton and Textile Sector in Egypt including its sub-sectors such as- cotton sub-sector and the textile and apparel sub-sector.